Fatty Acid Composition of Some New Varieties of Oil Seeds - Ingale, Satish; Shrivastava, S.K. (Asian Journal of Chemistry, 2010)
Five hybrid samples of oil seeds, viz., sunflower (Helianths annus) LSF -11, sunflower (Helianths annus) LSF-8, safflower (Carthamus tinctorius) PBNS-12, safflower (Carthamus tinctorius) PBNS-40 and 5 ground nut (Arachis hypogea) JL-24, have been studied for their fatty acid composition using gas chromatography. The JL-24 variety of ground nut has a rich (33.51 %) unsaturated fatty acid content with better storage quality, The percentage of total unsaturated fatty acids in gram samples lies in the sequence sunflower LSF-11 (24.78 %) > sunflower LSF- 8 (23.15 %) and in safflower PBNS-40 (20.62 %) > safflower PBNS -12 (10.68 %).